Investigation on performance and cost of combine harvester: case study at Kg Tengah, Padang Merlimau, Melaka paddy field / Muhammad Naziruldin Zubairy - Zubairy, Muhammad Naziruldin (Faculty of Plantation and Agrotechnology, 2019)
In Malaysia, using machinery in the plantation sector is the common technology that use in the field operation. The objective of this study is to investigate the performance and cost of ownership and operation cost of combine harvester, to evaluate the efficiency of combine harvester based on useful life and to help the owner to analyse data. Plus, to evaluate the cost based on age of combine harvester. This study observed at Tengah Padang Merlimau, Melaka paddy field. The primary data was collected to get the average of the combine harvester was harvested at an average speed at 4.92 km/HR. Besides, the secondary data were collected to estimate the operation area and determine the actual costs for five years of combine harvester useful life. The calculation was conducted by using formula and interpret in the total cost that required to spend in every years during harvesting operation in a paddy field. Based on motion study in order to determine the TFC, EFC and FE as measure the performance of combine harvester model New Holland S-1550. The average of TFC is 2.10 Ha/HR while the EFC was estimated at 1.22 Ha/HR or 5 Ton/HR and FE is 58.10% with average speed 4.92 Km/HR. By using the declining method, the percentage of depreciation was estimated at 84.8% decline in 5 years. Plus, the insurance, shelter, tax, and interest was assumed RM 8000 per year. However, the higher fixed cost in the year 2014 amounted RM 22.10 per ha. The higher operating cost was estimated in the year 2013 at contributed RM60.26 per ha. In this case, the ability of a machine is might be influenced towards another factor such as geographical factor, the machine condition and maintenance, labour skills and knowledge and more. Last, in this study can help the owner to produce actual data cost in future.